Effect of body size on the oral pharmacokinetics of oxytetracycline in rainbow trout (Oncorhynchus mykiss) - Orhan Corum; Erdinc Turk; Duygu Durna Corum; Ertugrul Terzi; Mustafa Cellat; Önder Yıldırım; Kamil Uney (PeerJ, 2024)
Objective The aim of this study was to determine the plasma pharmacokinetics of oxytetracycline (OTC) in rainbow trout (Oncorhynchus mykiss) of different body sizes. Methods The research was carried out on three groups as small (30–50 g), medium (90–110 g) and large (185–215 g) body sizes at 8 ± 0.5 °C. OTC was administered orally at a dose of 60 mg/kg to all groups. Blood samples were taken at 19 different sampling times until the 384 h after oxytetracycline administration. The plasma concentrations of OTC were measured using high pressure liquid chromatography-ultraviolet and pharmacokinetic parameters were evaluated using non-compartmental analysis. Results OTC was detected in small-body sized fish until the 336 h and in medium and large-body sized fish until the 384 h. The elimination half-life of OTC was 85.46, 87.24 and 86.98 h in the small, medium and large body size groups, respectively. The peak plasma concentration increased from 0.66 to 1.11 µg/mL, and the area under the plasma concentration-versus time curve from zero (0) h to infinity (∞) increased from 87.86 to 151.52 h*µg/mL, in tandem with the increase in fish body size. As fish body size increased, volume of distribution and total body clearance decreased. Conclusion These results show that the pharmacokinetics of OTC vary depending on fish size. Therefore, there is a need to reveal the pharmacodynamic activity of OTC in rainbow trout of different body sizes.
Keywords: QH301-705.5; R; Administration, Oral; Oxytetracycline; Body size; Anti-Bacterial Agents; Rainbow trout; Oncorhynchus mykiss; Aquaculture, Fisheries and Fish Science; Medicine; Animals; Body Size; Pharmacokinetics; HPLC; Biology (General); Chromatography, High Pressure Liquid; Half-Life